Augmentative and alternative communication for children with speech, language and communication needs. Issue 8 (August 2022) - Griffiths, Tom; Clarke, Michael; Price, Katie
Abstract: Augmentative and alternative communication (AAC) is the collective term for a broad range of techniques, strategies and devices which can support children with communication difficulties who may have little or no intelligible speech. This may include manual signs or systems of symbols, words or letters that can be used to construct messages and convey meaning. This review discusses the ways in which AAC systems are categorized and outlines some key principles of assessment and intervention, using the World Health Organization's International Classification of Functioning, Disability and Health for Children and Young People as a proposed framework to guide decision-making. The review is aimed at healthcare professionals working with children that may benefit from AAC. It highlights that children who may make use of AAC are a heterogeneous group and it is considered best practice for interventions to be highly individualized, taking into account the motor, sensory, learning and communication needs of each child, as well as their environment, personal preferences and support structures.